1956
DOI: 10.1152/physrev.1956.36.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Renewal of Cell Populations

Abstract: Following injection of an appropriate certain time, a proportion, p, of the 2N radioactive DNA precursor, suppose that labeled cells has transferred out of the after mitosis of the labeled cells in the basal layer. I f the transfer of the labeled basal layer of the esophagus, there are N cells is a random event, then the probabilpairs of labeled daughter cells or 2N ity that such a cell will transfer is p and labeled cells. Suppose further that at a the probability that it will not is 1 -p. __ -With one degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
135
0
5

Year Published

1957
1957
1977
1977

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(147 citation statements)
references
References 0 publications
5
135
0
5
Order By: Relevance
“…The thyroid belongs to that class of organs in which most of the adult parenchymatous cells survive the lifetime of the animal (Leblond and Walker, 1956). The human thyroid reaches adult size after puberty.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid belongs to that class of organs in which most of the adult parenchymatous cells survive the lifetime of the animal (Leblond and Walker, 1956). The human thyroid reaches adult size after puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, an attempt was made to obtain an understanding of the growth and regression of Graafian follicles from measurements of the volume and mitotic index of the granulosa of follicles of all sizes. From these data and a knowledge of the mitotic time it is possible to make estimates of the time intervals involved in .follicular grow~h (Leblond and Walker 1956). …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the normal matured salivary glands hardly showed mitotic figures (16). It was ob served that there were a slight increase in the mitotic changes of the enlarged acini during the treatment of ISO.…”
Section: Discussionmentioning
confidence: 93%